THE ECONOMIC RECOVERY OF CULINARY TRADERS IN PADANG CITY, WEST SUMATRA PROVINCE BASED ON THE SURVIVAL ANALYSIS METHOD - Rozalinda Rozalinda; Elvina Rahmi (Imara: JURNAL RISET EKONOMI ISLAM, 2023)
Background. The COVID-19 pandemic has had an impact on the economy, including small businesses engaged in the culinary sector as a result of the social restriction policy. Many small businesses experienced a decline in production and were even forced to go out of business..Purpose. This study aims to analyze how assistance from the government and family affects the economic recovery of culinary traders in Padang City, West Sumatra Province during the COVID-19 pandemic.Method. This study uses a quantitative approach.The analysis of the research data uses the survival analysis method, which is a form of research that seeks to obtain information on the development of a particular object within a certain time..Results. The results of the study prove that government assistance and family assistance have a positive and significant impact on the economic recovery of culinary traders in Padang City, West Sumatra Province during the COVID-19 pandemic. Thus, the higher government assistance and family assistance, the faster the economic recovery of culinary traders in Padang City during the COVID-19 pandemic. On the other hand, if government assistance and family assistance are not available, the economic recovery of culinary traders in Padang City during the COVID-19 pandemic will take longer.Conclusion. Based on survival analysis, it shows that the higher the government assistance, the faster the economic recovery for culinary traders in Padang City, West Sumatra Province. Vice versa. If government assistance is low, the economic recovery of traders will take longer. Based on survival analysis, the greater the family assistance, the faster the economic recovery for culinary traders in Padang City, West Sumatra Province. Vice versa, if family assistance is low, the economic recovery of traders will take longer.